2016
DOI: 10.1080/01635581.2016.1224365
|View full text |Cite
|
Sign up to set email alerts
|

Effects ofω-3 Fatty Acids and Catechins on Fatty Acid Synthase in the Prostate: A Randomized Controlled Trial

Abstract: Animal and human studies suggest fish oil and green tea may have protective effect on prostate cancer. Fatty acid synthase (FAS) has been hypothesized to be linked to chemoprotective effects of both compounds. This study evaluated the independent and joint effects of fish oil (FO) and green tea supplement (epigallocatechin-3-gallate, EGCG) on FAS and Ki-67 levels in prostate tissue. Through a double-blinded, randomized controlled trial with 2x2 factorial design, 89 men scheduled for repeat prostate biopsy foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 46 publications
(51 reference statements)
0
9
0
Order By: Relevance
“…As EGCG is found in green tea extracts, it is expected to be safe and feasible to investigate in clinical trials [170]. In addition, a clinical study has shown that EGCG regulates FASN expression and has effects on tumor control [171]. Although there are few reports on clinical trials of molecules that regulate amino acid metabolic enzymes, further studies on the regulation of amino acid metabolism in cancer cells are warranted.…”
Section: Clinical Significance Of Metabolic Regulation In Cancer Tmentioning
confidence: 99%
“…As EGCG is found in green tea extracts, it is expected to be safe and feasible to investigate in clinical trials [170]. In addition, a clinical study has shown that EGCG regulates FASN expression and has effects on tumor control [171]. Although there are few reports on clinical trials of molecules that regulate amino acid metabolic enzymes, further studies on the regulation of amino acid metabolism in cancer cells are warranted.…”
Section: Clinical Significance Of Metabolic Regulation In Cancer Tmentioning
confidence: 99%
“…It should be mentioned that results from randomized controlled trials regarding the effects of supplementation of fish oil (EPA and DHA acids) on prostate cancer prevention have not demonstrated significant findings [ 96 ]. Similarly, results obtained from a randomized controlled trial conducted by Zhang et al [ 97 ] among 86 men aged 50–78 years show a lack of a significant effect in Ki-67 protein expression (a marker of proliferation) in prostate tissue in men supplemented with fish oil (1.9 g of EPA and DHA per day for 60 days). A three-month randomized, double-blinded, clinical trial [ 98 ] investigating the effects of supplementation of 3 g of fish oil (containing 1,098 mg of EPA and 549 mg of DHA vs. a placebo) in a group of 69 men with low-burden prostate cancer demonstrated no differences in gene expression IGF-1 , IGF-1 receptor, and COX2 in prostate tissue when compared to a placebo.…”
Section: The Role Of Nutritional Factors and Foodstuffs On Prostatmentioning
confidence: 74%
“…Also, FAS gene was found to be upregulated by hypoxia in tumour cells. Therefore, overexpressed FAS appears to play important role in PCa [41]. As FAS is hypothesised to be associated with chemo-preventive effects of fish oil and green tea, Zhang et al (2016) evaluated their effects in PCa patients.…”
Section: Green Tea Phytochemicalsmentioning
confidence: 99%
“…Therefore, overexpressed FAS appears to play important role in PCa [41]. As FAS is hypothesised to be associated with chemo-preventive effects of fish oil and green tea, Zhang et al (2016) evaluated their effects in PCa patients. However, the results demonstrated no effects of fish oil and green tea supplement (EGCG) administered during a short duration on FAS or Ki67 in PCa [41].…”
Section: Green Tea Phytochemicalsmentioning
confidence: 99%